การแก้ไขสีภาพเพื่อจำลองสีลิปสติกบนริมฝีปาก - พรชนก ประสานศิลป์ (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
This project studied image colour correction for the simulation of lipstick colour on lips by means of correcting the RGB values for each channel separately using the opacity of lipstick. Five soft-matte lipstick colour samples were applied to the lips of three subjects with different skin tones. The images of the subjects with and without lipstick on their lips were taken. The colour correction was done on the images without any lipsticks. The source code in MATLAB was created to simulate mixing colours between lip colour and lipstick colour on the subjects’ lips. This process was done for each of the RGB channels separately and on a pixel-by-pixel basis. The accuracy of the lipstick colour simulation was tested via an online questionnaire. Observers compared images of subjects that applied lipstick with those with lipstick colour simulation. They were asked whether the simulations were acceptable as well as to rate the similarity. Ninety-one observers participated in the experiment. It was found that the opacity values of different lipstick samples were similar. The accuracy of the lipstick colour simulation was moderate. The subjects’ lips influenced the colour simulation accuracy. The simulation images with an unnatural lip shape and the shape that did not fit the actual lip shape affected observers’ decisions.